Konsep Pendidikan Multikulturalisme Dalam Pendidikan Anak Usia Dini: Kajian Konsep - Aliamran (Medan Resource Center, 2022)
This essay examines the topic of multiculturalism education as it relates to early childhood education: In studies, since the creation of this title, there have been numerous instances in which society has taught young children lessons that are unsuitable. The most recent instance is a children's carnival. Researchers believe that this teaching has gone beyond the bounds of Islamic teachings, which are rahmatal lilalamin. As a result, we need to make a concept of multiculturalism education studies in early childhood education. The first two questions are: how is the concept of multiculturalism itself, and how is the concept of early childhood education? Third, how is multiculturalism included into early childhood education? the idea of multicultural education, early childhood education, and multicultural notions in early childhood education are all explained utilizing a content analysis technique.